PUTUSAN HAKIM TENTANG REHABILITASI TERHADAP PECANDU NARKOTIKA (Studi Putusan Nomor : 35/PID/2012/PT.TK) - DewiMaya Benadicta Barus; Mahmud Mulyadi; Suhaidi Suhaidi; Syafruddin Sulung Hasibuan (Universitas Sumatera Utara, 2016)
ABSTRACT Narcotic addict when viewed from the aspect of health, they were of the sick or in other words people who suffer pain. Therefore, the corresponding incarcerate isn't the right solution. Supreme Court circulars (SEMA) number 4 of 2010 can be used as a basis for reasoning or reference the judge in meting out sanctions and rehabilitation. As for the problems formulated in this thesis writing is why rehabilitation of narcotic addicts are deemed necessary as the basis for an alternative to criminal action, and then discussed again what was the background to the legal considerations the judge in meting out the rehabilitation decision in connection with any criminal action. Research methods used by the author in writing this is the juridical normative research method, which is based on secondary data and put emphasis on measures of speculative theoretical-normative analysis-qualitative and. As for the data used in compiling the writing was obtained from the research libraries (library research). As a technique of collecting data by utilizing a wide range of literature in the form of legislation, books, scientific papers, lecture materials, court rulings, as well as secondary data sources discussed by other authors. Considered necessary for the rehabilitation of addicts of narcotic drugs as an alternative to criminal action because of it's own rehabilitation aims to improve the health of the addicts of narcotic drugs with care and rehabilitation on an existing rehabilitation centres. This is compared to the upside if the addict of narcotics is punished by criminal sanctions. As for the background of the legal considerations of the overthrow of the ruling of the judge in connection with any rehabilitation criminal action is by observing the values of certainty, justice and benefit based on a notion that the narcotic addicts as victims of crime so more suitable rehabilitation sanctions meted out verdict that will provide care and guidance that is educating and improving physically and mentally from the addict. Key words : rehabilitation, narcotics addicts, the verdict of the judge.